A hybrid approach for multi-view modeling - Cicchetti, Antonio; Ciccozzi, Federico; Leveque, Thomas (Electronic Communications of the EASST, 2012)
Multi-view modeling is a widely accepted technique to reduce the complexity in the development of modern software systems. It allows developers to focus on a narrowed portion of the specification dealing with a selected aspect of the problem. However, multi-view modeling support discloses a number of issues: on the one hand consistency management very often has to cope with semantics interconnections between the different concerns. On the other hand, providing a predefined set of views usually results as too restrictive because of expressiveness and customization needs. This paper proposes a hybrid solution for multi-view modeling based on an arbitrary number of custom views defined on top of an underlying modeling language. The aim is to benefit from the consistency by-construction granted by well-defined views while at the same time providing malleable perspectives through which the system under development can be specified.